Spin-bath polarization via disentanglement - D D Bhaktavatsala Rao; Arnab Ghosh; David Gelbwaser-Klimovsky; Nir Bar-Gill; Gershon Kurizki (New Journal of Physics, 2020)
The occurrence of any physical process is restricted by the constraints imposed by the laws of thermodynamics on the energy and entropy exchange involved. A prominent class of processes where thermodynamic constraints are crucial involve polarization of nuclear spin baths that are at the heart of magnetic resonance imaging, nuclear magnetic resonance (NMR), quantum information processing. Polarizing a spin bath, is the key to enhancing the sensitivity of these tools, leading to new analytical capabilities and improved medical diagnostics. In recent years, significant effort has been invested in identifying the far-reaching consequences of quantum modifications to classical thermodynamics for such processes. Here we focus on the adverse role of quantum correlations (entanglement) in the spin bath that can impede its cooling in many realistic scenarios. We propose to remove this impediment by modified cooling schemes, incorporating probe-induced disentanglement or, equivalently, alternating non-commuting probe–bath interactions to suppress the buildup of quantum correlations in the bath. The resulting bath polarization is thereby exponentially enhanced. The underlying quantum thermodynamic principles have far-reaching implications for a broad range of quantum technological applications.